2023
DOI: 10.1073/pnas.2216397120
|View full text |Cite
|
Sign up to set email alerts
|

A PDLP-NHL3 complex integrates plasmodesmal immune signaling cascades

Abstract: The plant immune system relies on the perception of molecules that signal the presence of a microbe threat. This triggers signal transduction that mediates a range of cellular responses via a collection of molecular machinery including receptors, small molecules, and enzymes. One response to pathogen perception is the restriction of cell-to-cell communication by plasmodesmal closure. We previously found that while chitin and flg22 trigger specialized immune signaling cascades in the plasmodesmal plasma membran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 47 publications
0
8
0
Order By: Relevance
“…Interestingly, PDLP1 and PDLP5 have recently been shown to be part of a protein complex with the immune regulatory protein NDR1/HIN1-LIKE 3 (NHL3), which mediates CalS1-dependent callose and defense-related plasmodesmatal closure. 41 However, PDLP5, unlike PDLP1, did not co-localize with Hpa haustoria, while NHL3 was not identified as a direct interactor with PDLP1, suggesting that PDLP1 acts through a different signaling complex to regulate Hpa -induced callose. 22 Our finding that BABA primes PDLP1 localization at the onset of PMR4-dependent penetration resistance provides further evidence for a specific defense regulatory role of this protein in the Arabidopsis- Hpa interaction.…”
Section: Discussionmentioning
confidence: 85%
“…Interestingly, PDLP1 and PDLP5 have recently been shown to be part of a protein complex with the immune regulatory protein NDR1/HIN1-LIKE 3 (NHL3), which mediates CalS1-dependent callose and defense-related plasmodesmatal closure. 41 However, PDLP5, unlike PDLP1, did not co-localize with Hpa haustoria, while NHL3 was not identified as a direct interactor with PDLP1, suggesting that PDLP1 acts through a different signaling complex to regulate Hpa -induced callose. 22 Our finding that BABA primes PDLP1 localization at the onset of PMR4-dependent penetration resistance provides further evidence for a specific defense regulatory role of this protein in the Arabidopsis- Hpa interaction.…”
Section: Discussionmentioning
confidence: 85%
“…Plasmodesmal closure is an early reaction, initiated within 30 minutes upon perceiving pathogen-derived molecules and stress-associated signals including SA and hydrogen peroxide (Xu et al 2017;Cheval et al 2020;Tee et al 2023b), and is critical for the execution of a full response. Thus, we reason that plasmodesmal closure regulates a range of downstream processes.…”
Section: Discussionmentioning
confidence: 99%
“…The decrease in plasmodesmal aperture in response to stress is a process activated by signaling cascades mediated by specific machinery. For example, LYSM-CONTAINING GPI-ANCHORED PROTEIN 2 (LYM2; Faulkner et al 2013) and CALMODULIN-LIKE 41 (CML41;Xu et al 2017) specifically mediate plasmodesmal responses to the microbial elicitors chitin and flg22 respectively, and 3 PLASMODESMATA LOCATED PROTEIN 5 (PDLP5) integrates these responses, as well as plasmodesmal responses triggered by the defense hormone salicylic acid (SA; Wang et al 2013;Tee et al 2023b). The observation that lym2 mutants cannot close their plasmodesmata in response to chitin but execute normal chitin-triggered mitogenactivated protein kinase (MAPK) activation and apoplastic ROS production (Faulkner et al 2013) indicates that plasmodesmal signaling cascades can act independently of other responses.…”
Section: Introductionmentioning
confidence: 99%
“…Several family members are typically encoded in a plant genome, and different members can have a tissue or context-specific role at plasmodesmata [ 68 , 72 , 73 , 74 ]. Several accessory proteins with regulatory functions have been identified that can integrate internal and external cues and relay them toward enzymes affecting callose homeostasis [ 68 , 75 ]. Such changes typically take place on the timescale of minutes.…”
Section: Setting the Stage For Intercellular Transport: Biogenesis An...mentioning
confidence: 99%